Chromosome-level genome assembly of goose provides insight into the adaptation and growth of local goose breeds. (3rd February 2023) - Zhao, Qiqi; Lin, Zhenping; Chen, Junpeng; Xie, Zi; Wang, Jun; Feng, Keyu; Lin, Wencheng; Li, Hongxin; Hu, Zezhong; Chen, Weiguo; Chen, Feng; Junaid, Muhammad; et al.
Abstract: Background: Anatidae contains numerous waterfowl species with great economic value, but the genetic diversity basis remains insufficiently investigated. Here, we report a chromosome-level genome assembly of Lion-head goose ( Anser cygnoides ), a native breed in South China, through the combination of PacBio, Bionano, and Hi-C technologies. Findings: The assembly had a total genome size of 1.19 Gb, consisting of 1, 859 contigs with an N50 length of 20.59 Mb, generating 40 pseudochromosomes, representing 97.27% of the assembled genome, and identifying 21, 208 protein-coding genes. Comparative genomic analysis revealed that geese and ducks diverged approximately 28.42 million years ago, and geese have undergone massive gene family expansion and contraction. To identify genetic markers associated with body weight in different geese breeds, including Wuzong goose, Huangzong goose, Magang goose, and Lion-head goose, a genome-wide association study was performed, yielding an average of 1, 520.6 Mb of raw data that detected 44, 858 single-mucleotide polymorphisms (SNPs). Genome-wide association study showed that 6 SNPs were significantly associated with body weight and 25 were potentially associated. The significantly associated SNPs were annotated as LDLRAD4, GPR180, and OR, enriching in growth factor receptor regulation pathways. Conclusions: We present the first chromosome-level assembly of the Lion-head goose genome, which will expand the genomic resources of the Anatidae family, providing a basis for adaptation and evolution. Candidate genes significantly associated with different goose breeds may serve to understand the underlying mechanisms of weight differences.